Dynamic model and load sharing performance of planetary gear system with journal bearing. (September 2020) - Zhang, Chunpeng; Wei, Jing; Wang, Feiming; Hou, Shaoshuai; Zhang, Aiqiang; Lim, Teik C.
Highlights: A dynamic model for PGS with journal bearing and flexible structure is established. Impact of differences of journal bearing on load sharing characteristics is studied. Effect of flexible ring gear and pin on load sharing performance are compared. Influence of installation form of bearing with error on load sharing is explored. Abstract: Owing to its advantages of a small size, excellent vibration resistance, and smooth operation, journal bearing is widely used in planetary gear systems (PGSs). When there are errors in the journal bearing, the load sharing performance (LSP) of the system is significantly affected. A dynamic model is established to study the influence of journal bearing with errors on the load sharing characteristics of the PGS. The dynamic characteristics of the journal bearing and the flexibility of the ring gear and pin are also considered. The characteristics of the journal bearing and influence of the working conditions and flexible structure on the load sharing characteristic are analyzed. The installation forms of the bearing with different clearance ratios are classified, and the load sharing characteristics of the system under different installation forms are explored. The results indicate that load sharing characteristics are related to the parameters of the journal bearing. Compared with the flexibility of the ring gear, the pin has a limited impact on the load sharing characteristics of the system. The LSP of the adjacent installation mode of a journal bearing with errors is better than that of the interval installation mode.